Pendampingan Digitalisasi UMKM Menuju Ekonomi Berbasis Teknologi di Desa Sukarame, Kecamatan Leles, Kabupaten Garut - Hermawan, Wawan; Iqbaludin (Indra Institute Research & Publication, 2025)
Digital transformation has become essential for enhancing competitiveness and sustainability of MSMEs, particularly in rural areas. This community service activity aims to improve the capacity of MSME actors in Sukarame Village, Leles District, Garut Regency, through mentoring and business digitalization training. The method employed is a participatory approach based on non-formal education, involving 25 MSME actors through five stages: digitalization socialization, technical training on social media and marketplace, product identity creation, participatory observation, and impact evaluation. Results demonstrate significant improvements in digital literacy, ability to manage business social media accounts, product identity awareness, and average revenue increase within three months post-training. Despite facing infrastructure constraints and human resource limitations, this activity successfully established a foundation for community-based digital MSME ecosystem. These findings confirm that MSME digitalization can serve as an effective village economic empowerment strategy when facilitated through contextual approaches, intensive mentoring, and continuous support from various stakeholders.